Percepção dos frentistas de postos de combustíveis sobre as repercussões de sua atividade profissional na sua saúde, na cidade de Uberaba - Portes, Márcia do Nascimento (2008)
The present study has been approved by the Committee for Ethics in Research with Human Beings at UFU, in September 2006, report nº 266/06. It seeks to testify how aware workers of gas stations in the city of Uberaba, Minas Gerais, are of the impact of their working conditions in their own health. In this study, we present the results of a survey questionnaire applied to 107 gas station attendants. The contamination of workers in gas stations has become an object for researches which relates working activities to the worker s health. The number of individuals exposed to gas is too large and includes, mostly, employees of oil companies and gas station attendants. In this work, a questionnaire was applied semi-structured for the gas station attendants of Uberaba and it was observed that a good part of these gas station attendants doesn't have knowledge on Biosafety conditions of their work. The results reinforce the need of implantations of Biosafety courses. Therefore, the research undergone with these workers and the release of its results, aims to minimize and prevent possible contamination by fuel to this class of professional.